2023
DOI: 10.3389/fpls.2023.1202775
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a novel QTL DM9.1 conferring downy mildew resistance in melon

Abstract: Downy mildew (DM) is a major foliar disease globally causing great economic loss in melon production. Utilizing disease-resistant cultivars is the most efficient approach for disease control, while discovery of disease-resistant genes is crucial for the success of DM-resistant breeding. To address this problem, two F2 populations were constructed using the DM-resistant accession PI 442177 in this study, and QTLs conferring DM resistance were mapped using linkage map and QTL-seq analysis, respectively. A high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Transcriptomic analysis by Ling et al [ 152 ] revealed 293 genes upregulated in the resistant to downy mildew (DM) cultivar PI 442177 in comparison to the susceptible landrace ‘Huangtu’, while significant enrichment was also observed in pathways associated with defense response in PI 442177. Moreover, two landraces, ‘Huangtu’ and ‘Huangdanzi’, susceptible to DM were used with PI 442177, to produce F 2 populations for linkage analysis, resulting in the identification of a major QTL, DM9.1 , for DM resistance on Chr9 [ 153 ]. Landraces from different geographic regions were used by Oumouloud et al [ 154 ] to develop functional markers that would improve MAS for the melon Fusarium wilt resistance gene ( Fom-2 ).…”
Section: Application Of New Genomic Technologies In Landraces and Ind...mentioning
confidence: 99%
“…Transcriptomic analysis by Ling et al [ 152 ] revealed 293 genes upregulated in the resistant to downy mildew (DM) cultivar PI 442177 in comparison to the susceptible landrace ‘Huangtu’, while significant enrichment was also observed in pathways associated with defense response in PI 442177. Moreover, two landraces, ‘Huangtu’ and ‘Huangdanzi’, susceptible to DM were used with PI 442177, to produce F 2 populations for linkage analysis, resulting in the identification of a major QTL, DM9.1 , for DM resistance on Chr9 [ 153 ]. Landraces from different geographic regions were used by Oumouloud et al [ 154 ] to develop functional markers that would improve MAS for the melon Fusarium wilt resistance gene ( Fom-2 ).…”
Section: Application Of New Genomic Technologies In Landraces and Ind...mentioning
confidence: 99%
“…Experiments were conducted to assess the responses of 'K10-1 and 'K10-9 to P. cubensis inoculation at both seedling and mature stages, following the artificial inoculation procedure described by Zhang et al [2]. Each experiment incorporated a minimum of 3 biological replicates, with 30 plants from each cultivar per replicate.…”
Section: Plant Materials and Treatmentmentioning
confidence: 99%
“…Each experiment incorporated a minimum of 3 biological replicates, with 30 plants from each cultivar per replicate. Once the first true leaf fully expanded, seedlings were inoculated with P. cubensis using a spray method, in accordance with Zhang et al [2]. The spore concentration for inoculation was set at 5 × 10 3 spores/mL or higher, supplemented with 0.5 ‰ Tween, while double-distilled water (ddH 2 O) served as the control.…”
Section: Plant Materials and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations